Capital Structure Effects: The Role of Sales Growth in Shaping Firm Performance Across Southeast Asia - Prabowo, Ananto (JASF: Journal of Accounting and Strategic Finance, 2025)
Purpose: This study aims to explore the relationship between capital structure and firm performance among listed firms in Southeast Asia and examines whether sales growth changes that relationship, a topic in response to the lack of studies focused on this region. Method: This study uses an unbalanced panel dataset of 4,229 listed firms in Southeast Asia, including Indonesia, Malaysia, the Philippines, Thailand, Singapore, and Vietnam from 2019 to 2023. The study employed panel data regression analysis with Stata 19. Findings: The findings show important patterns in capital structure and performance. Leverage to equity consistently shows a negative relationship with ROA, ROE, and Tobin’s Q, indicating its detrimental effect on performance. Leverage to assets produces mixed results, while market value leverage is mostly positive. Sales growth plays a moderating role by strengthening the positive and significant impact of market value leverage on performance and reshapes other relationships. These results highlight the complexity of capital structure decisions and the influence of sales growth on capital structure and firm performance relationship in Southeast Asia Implications: This research extends the trade-off theory by empirically showing that the optimal capital structure is a quantifiable result influenced by various leverage mechanisms. Sales growth becomes as a critical moderator, strengthening a firm’s ability to manage financial risk and shift the trade-off point toward more favorable leverage. This implies that capital structure does not remain fixed; it moves with growth expectations. Practically, firms with higher sales growth likely to adjust leverage when conditions change, which in turn reduces the likelihood of financial risks. Novelty/Value: This research introduces a new perspective by examining sales growth as a moderating factor in the relationship between capital structure and firm performance. Additionally, by using multiple measures of performance (ROA, ROE, Tobin’S Q) and capital structure (LE, LA, MVL) in the context of emerging markets, the research offers insights that are both new and practical.